Perspectives on long-acting injectable HIV antiretroviral therapy at an alternative care site: a qualitative study of people with HIV experiencing substance use and/or housing instability - Laura Fletcher; Shana A. B. Burrowes; Ghulam Karim Khan; Lora Sabin; Samantha Johnson; Simeon D. Kimmel; Glorimar Ruiz-Mercado; Cassandra Pierre; Mari-Lynn Drainoni (Harm Reduction Journal, 2023)
Abstract Introduction Adherence to daily oral antiretroviral therapy (ART) and regular clinic appointments can be challenging for individuals who experience adverse social determinants of health. Long-acting injectable ART administered outside of traditional clinic settings may be a promising solution to adherence barriers, but additional research is needed to assess patients’ perspectives. This study assessed perspectives of people living with HIV (PLWH) who had difficulty with adherence to traditional HIV care models and evaluated feasibility and acceptability of receiving a long-acting ART injection at a location outside of a traditional HIV clinic to address barriers to HIV care. Methods Qualitative interviews (n = 26) were conducted with PLWH who had experienced barriers to adherence. Participants were referred to the study by staff from Project Trust, a drop in harm reduction and sexually transmitted infection/HIV clinic. The interviews were conducted between May and November 2021. Interviews were recorded, professionally transcribed, coded, and analyzed qualitatively using the integrated-Promoting Action on Research Implementation in Health Services framework. Results We identified 6 main themes regarding the acceptability of receiving a long-acting injection to treat HIV, and the acceptability and feasibility of receiving injections at an alternative care site. Participants specified that they: (1) have a general understanding about their HIV care and the importance of ART adherence, (2) prefer a long-acting injection over a daily pill regimen, (3) expressed concerns about injection safety and efficacy, (4) had specific logistical aspects around the delivery of long-acting injections, including location of injection administration, that they believed would improve their ability to adhere, (5) have confidence that they can become undetectable and then complete the oral lead-in required to begin receiving the injection, and (6) see potential barriers that remain a concern for successful adherence to long-acting injections. Conclusion To better treat HIV among people who are living with challenging social determinants of health, interventions that include a long-acting injection in a non-traditional care setting may prove to be a promising treatment option.